On the potential of ultrasound elastography for pressure ulcer early detection - Deprez, Jean-François; Brusseau, Elisabeth; Fromageau, Jérémie; Cloutier, Guy; Basset, Olivier (Medical physics (Lancaster), 2011)
Purpose: Pressure ulcers are areas of soft tissue breakdown induced by a sustained mechanical stress that damages the skin and underlying tissues. They represent a considerable burden to the society in terms of health care and cost. Yet, techniques for prevention and detection of pressure ulcers still remain very limited. In this article, the authors investigated the potential of ultrasound elastography for pressure ulcer early detection. Elastography is an imaging technique providing local information on biological tissue mechanical properties. It is relevant for pressure ulcer detection as this pathology is associated with a gradual stiffening of damaged tissues, beginning in the deeper tissues and progressing toward the skin surface. Methods: A 2D ultrasound elastography method was proposed and its ability in terms of pressure ulcer detection was validated through numerical simulations and physical acquisitions on pressure ulcer mimicking phantoms.In vivo experiments on a rat model are also reported. A maintained pressure was applied on the animal thigh, with a view to generate a pressure ulcer, and ultrasound data were acquired and processed before and after application of this pressure. Results: Numerical simulations demonstrated that a pressure ulcer can theoretically be detected at a very early stage with ultrasound elastography. Even when the ulcer region was characterized by a low stiffening (ratio of 1.8 relative to normal tissues), the corresponding elastogram clearly underlined the pathological area. This observation was confirmed by the results obtained on a physical phantom mimicking a pressure ulcer at an early stage. Computed elastograms showed strain differences between areas mimicking healthy and pathological tissues. Results corresponding toin vivo experiments revealed a difference in the way tissues behaved before and after the pressure was applied on the animal thigh, which strongly suggests the presence of a pathological area. Conclusions: Experiments demonstrated that ultrasound elastography is a promising technique for pressure ulcer detection, especially at an early stage of the pathology, when the disease is still visually undetectable. In the absence of any gold standard method, this is also a first step toward the development of a quantitative technique.